2010
DOI: 10.1021/ac101856r
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Detection and Identification of Glycopeptides in Negative Ion Mode Mass Spectrometry

Abstract: A combined MS and MS/MS approach implemented with MALDI FT-ICR MS in the negative ion mode is described for enhanced glycopeptide detection and MS/MS analysis. Positive ion mode mass spectrometry (MS) analysis is widely used for glycopeptide characterization, but the analyses are hampered by potential charge-induced fragmentation of the glycopeptides and poor detection of the glycopeptides harboring sialic acids. Furthermore, tandem MS analysis (MS/MS) via collision-induced dissociation (CID) of glycopeptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 35 publications
1
56
0
Order By: Relevance
“…Aside from the analytical problems related to the separation and analysis of glycans, the additional challenges in analysis of glycopeptides are: (i) presence of the peptide backbone, (ii) identification of glycopeptides (typically mixed with peptides), (iii) identification of glycosylation sites, (iv) identification of glycan structures, and (v) characterization of microheterogeneity of glycosylation. Negative ion mode MALDI MS/MS has been successfully applied for analysis of N-glycopeptides [78]. MALDI MS allows detailed MS/MS characterization of small biomolecules, but it lacks efficient separation of isomers capability.…”
Section: Ms Analysis Of N-glycans and N-glycopeptidesmentioning
confidence: 99%
See 3 more Smart Citations
“…Aside from the analytical problems related to the separation and analysis of glycans, the additional challenges in analysis of glycopeptides are: (i) presence of the peptide backbone, (ii) identification of glycopeptides (typically mixed with peptides), (iii) identification of glycosylation sites, (iv) identification of glycan structures, and (v) characterization of microheterogeneity of glycosylation. Negative ion mode MALDI MS/MS has been successfully applied for analysis of N-glycopeptides [78]. MALDI MS allows detailed MS/MS characterization of small biomolecules, but it lacks efficient separation of isomers capability.…”
Section: Ms Analysis Of N-glycans and N-glycopeptidesmentioning
confidence: 99%
“…The biggest drawbacks of LC-MS analyses of released N-glycans are twofold: (i) loss of information about N-glycosylation sites on proteins from which the N-glycans were released; and (ii) loss of information about N-glycosylation microheterogeneity patterns on N-glycosylation sites on respective proteins. This information can be obtained using MALDI MS/MS approach, as shown in Figure 17, on example of bovine lactoferrin [78]. Such glycoprotein samples are extremely complex to analyze using MS, especially when present in complex glycoproteomic sample mixtures.…”
Section: Ms Analysis Of N-glycans and N-glycopeptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, Nwosu et al reported on the enhanced detection of relatively short glycopeptides in the negative-ion mode, compared to the positive-ion mode. 53) Despite its potential usefulness in detecting glycopeptide signals, little information is available in terms of our understanding of the fragmentation of deprotonated glycopeptides. So far, a greater production of di erent fragment ions has been reported than in positive-ion mode.…”
Section: Negative-ion Fragmentation Of Glycopeptidesmentioning
confidence: 99%